REMOVAL OF OIL AND GREASE FROM AN OIL REFINERY EFFLUENT - S.Naseri; GH. Mostafaee (Tehran University of Medical Sciences, 1997)
In this research performed during 1993-1994, the effluent of Behran Oil Refmery, in south of Tehran, which produces different types of industrial oil and greases, was studied and 3 methods of gravity separation, coagulation and flocculation and dissolved air flotation were investigated. In the first phase of the survey, the quality and quantity of the effluent were determined. This showed an average daily flow rate of 302 m3, pH 9.03, and average concentration of 314.84, 3330, 200, 1726 and 34.5 mg/l, respectively for oil, COD, SS, TS and furfural. In the second phase, the efficiency of abovementioned treatment methods were as follows: Applying gravity separation with the detention time of 180 mm, removal percentages for COD, SS and greases were 30.3%, 52.5% and 49.6%, respectively. Applying coagulation and flocculation following gravity separation different coagulants (alum, lime and ferric chloride) were used and their treatment efficiencies were evaluated. Lime showed the highest efficiency of 64% and 85.4%, for grease and COD removal, respectively in pH 11. Dissolved air flotation (DAF), which was conducted in the pressure of 3 bars, showed average removal percentages of 9l.96% and 79.17%, for the oil and COD, respectively. So, this system may be chosen as the most efficient one in oil and grease removal producing an effluent which may be fed to a biological treatment unit to remove other pollutants such as ROD and COD.